2017
DOI: 10.1097/rli.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

An Image-Domain Contrast Material Extraction Method for Dual-Energy Computed Tomography

Abstract: Objectives Conventional material decomposition techniques for dual-energy CT (DECT) assume mass or volume conservation, where the CT number of each voxel is fully assigned to predefined materials. We present an image-domain contrast material extraction process (CMEP) method that preferentially extracts contrast-producing materials while leaving the remaining image intact. Materials and Methods Image processing freeware (Fiji) is used to perform consecutive arithmetic operations on a dual-energy ratio map to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Advances in dual-energy CT (DECT)-related material decomposition may allow to overcome this problem: DECT has the ability to differentiate between iodine and calcium contents by using differences in energy dependence of CT attenuation. [5][6][7][8][9] Previous studies have compared the efficiency of plaque and bone removal in DECT angiography of cervical vessels with that of conventional CTA and have found advantages for DECT regarding a reduction of reading time and radiation dose. 6,[10][11][12][13] Other studies have reported the feasibility and utility of bone and plaque removal in intracranial and cervical DECT angiography examinations compared with DSA 14,15 and the accurate classification of hemorrhagic and calcified cerebral lesions.…”
mentioning
confidence: 99%
“…Advances in dual-energy CT (DECT)-related material decomposition may allow to overcome this problem: DECT has the ability to differentiate between iodine and calcium contents by using differences in energy dependence of CT attenuation. [5][6][7][8][9] Previous studies have compared the efficiency of plaque and bone removal in DECT angiography of cervical vessels with that of conventional CTA and have found advantages for DECT regarding a reduction of reading time and radiation dose. 6,[10][11][12][13] Other studies have reported the feasibility and utility of bone and plaque removal in intracranial and cervical DECT angiography examinations compared with DSA 14,15 and the accurate classification of hemorrhagic and calcified cerebral lesions.…”
mentioning
confidence: 99%
“…The Contrast Material Extraction Process (CMEP) selectively extracts contrast producing materials in the dataset based on their dual energy ratio; the ratio of CT numbers from low to high x-ray energies (25). Thresholded masks are created from the dual energy ratio map, and are subsequently applied to original CT images to generate material specific images.…”
Section: Methodsmentioning
confidence: 99%
“…While the utility of high-Z contrast agents has been shown in preclinical animal models of abdominal disease (21, 22), their performance for quantitative separation tasks such as CACS remain unknown. Also, novel algorithms to separate contrast material signal from calcium at DECT have been described (23, 24), and include the contrast material extraction process (CMEP) (25). CMEP, an image domain material separation method that offers an alternative to conventional material decomposition (MD), showed accurate separation of contrast agent signals in a phantom study (25), but has not been tested for CACS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of material-specific image produced by DECT attaches great importance to the elaborated design of the basis material decomposition method. The existing decomposition methods can be divided into two main categories: projection-based [ 5 – 7 ] and image-based [ 8 10 ]. Projection-based methods pass the projection data through a decomposition function, followed by image reconstruction such as filtered backprojection (FBP).…”
Section: Introductionmentioning
confidence: 99%